2022
DOI: 10.1038/s41418-022-01016-w
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial de-differentiation triggered by co-ordinate epigenetic inactivation of the EHF and CDX1 transcription factors drives colorectal cancer progression

Abstract: Colorectal cancers (CRCs) often display histological features indicative of aberrant differentiation but the molecular underpinnings of this trait and whether it directly drives disease progression is unclear. Here, we identify co-ordinate epigenetic inactivation of two epithelial-specific transcription factors, EHF and CDX1, as a mechanism driving differentiation loss in CRCs. Re-expression of EHF and CDX1 in poorly-differentiated CRC cells induced extensive chromatin remodelling, transcriptional re-programmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…Likewise, studies have found EHF to be an important tumor suppressor in the prostate and pancreas via promotion of differentiation and inhibition of EMT, which impedes metastasis and is rescued by re-expression of EHF [ 81 83 ]. Similar findings have been observed for colorectal and head and neck squamous cell carcinomas [ 79 , 84 ]. Hence, AR-GATA3 mediated up-regulation of EHF in breast cancer cells may play a key role in mediating the tumor suppressor activity associated with AR signaling.…”
Section: Discussionsupporting
confidence: 88%
“…Likewise, studies have found EHF to be an important tumor suppressor in the prostate and pancreas via promotion of differentiation and inhibition of EMT, which impedes metastasis and is rescued by re-expression of EHF [ 81 83 ]. Similar findings have been observed for colorectal and head and neck squamous cell carcinomas [ 79 , 84 ]. Hence, AR-GATA3 mediated up-regulation of EHF in breast cancer cells may play a key role in mediating the tumor suppressor activity associated with AR signaling.…”
Section: Discussionsupporting
confidence: 88%
“…The inhibition of HO-1 by ZnPP or its siRNA-mediated knockdown further increased the hemin-induced ROS formation and toxicity. HCT116 CRC cells were characterized as a non-differentiated cell line, classified as stage 3 of the TNM system [175,176] with low basal HO-1 levels, which is in accordance As mentioned above, the interrelation of heme, ROS and HO-1 was shown for both non-tumor as well as CRC cells. Nevertheless, non-malignant HCEC were more sensitive to hemin than CRC cells (HCT116 cells and others) as demonstrated by higher ROS levels, oxidative DNA damage, and cytotoxicity [21].…”
Section: Ho-1-dependent Protection Against Ros and Lipid Peroxidationsupporting
confidence: 70%
“…Chemoresistance remains a major challenge in oncology [ 40 ]. Different molecular mechanisms are involved in mediating resistance to therapy including, (i) reduction in intracellular concentrations of drugs; (ii) alteration in the molecular drug targets; (iii) enhanced DNA repair; (iv) stimulation of survival mechanisms, (v) epithelial to mesenchymal transition [ 41 43 ] and inhibition of (vi) cell death. In HCC, more than 100 genes are implicated in regulating chemoresistance and have been classified into seven groups from Mechanisms of Chemoresistance 1 (MOC-1) to MOC-7 [ 44 ].…”
Section: Resultsmentioning
confidence: 99%